Preparation of monodisperse bimetallic nanorods with gold nanorod core and silver shell and their plasmonic property and SERS efficiency. (9th May 2014) - Dong, Xu; Zhou, Jianfeng; Liu, Xiaoyun; Lin, Danli; Zha, Liusheng
<x xml:space="preserve">Abstract</x> In this study, monodisperse bimetallic nanorods with gold (Au) nanorod core and silver (Ag) shell (Au@AgNRs) were synthesized through seed‐mediated growth process by reduction of AgNO3 using Au nanorods with narrow size and shape distribution as seeds. With increasing the used amount of AgNO3, the Ag shell thickness of their lateral facets is raised faster than that of their two tips, leading to a decrease of their aspect ratios. Four plasmon bands are observable on the extinction spectra of Au@AgNRs, which are attributed to the longitudinal dipolar plasmon mode, transverse dipolar plasmon mode, and octupolar plasmon mode of the core‐shell structured bimetallic nanorods, respectively. As their Ag shell thickness increases, their longitudinal plasmon band blue‐shifts notably with the transverse plasmon band blue‐shifting and the two octupolar plasmon bands red‐shifting slightly, due to the decrease of their aspect ratios and enhancement of Ag plasmon resonance contribution. When used as surface‐enhanced Raman scattering (SERS) substrate for probing minute amounts of 4‐mercaptobenzoic acid in aqueous solution, Au@AgNRs have much stronger SERS activity than Au nanorods, and the obtained Raman signals are highly reproducible arising from their excellent monodispersity. Their SERS activity is remarkably increased with their Ag shell thickness thanks to the enhancing surface electric field and the chemical enhancement associated with electronic ligand effect. Copyright © 2014 John Wiley & Sons, Ltd.